Вплив психологічних особливостей особистості на тактику проведення судово-психіатричної експертизи - Макарова, О. П.; Makarova, O. P.; Olena Makarova (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 1. - С. 167-179, 2024)
Проаналізовано вплив психологічних особливостей особистості обвинуваченого на тактику проведення судово-психіатричної експертизи. Досліджено конкретні аспекти особистісного складу особистості, що можуть впливати на результати експертизи та як це враховується під час її проведення. Зроблено акцент на взаємодії психологічних чинників із правовими процесами та можливості їх урахування для забезпечення об’єктивності й точності судових вироків. Проаналізовано практичні аспекти роботи експертів у сфері судової психіатрії та надано рекомендації щодо оптимізації процесу проведення експертизи з урахуванням психологічних особливостей особистості обвинуваченого.

The article examines the influence of psychological characteristics of a personality on the tactics of forensic psychiatric examination. A forensic psychiatric examination is a comprehensive study of a person’s mental state, which is carried out with the aim of establishing the person’s ability to bear responsibility for his or her actions. The results of the examination may have a significant impact on the course of criminal proceedings and the determination of the penalty. In addition to the mental disorder, the results of the examination may also be influenced by the psychological characteristics of the defendant's personality. Psychological features of a person are stable individual psychological characteristics that determine a person’s behaviour in different situations. They include such properties as temperament, character, emotionality, will, personality orientation, intelligence, value orientations, etc. These characteristics can affect how the defendant perceives the examination situation, how he or she behaves with the expert, how he or she answers questions, and how he or she assesses his or her own mental state. Understanding the psychological characteristics of the defendant's personality allows the expert to: optimise the examination methodology, i.e. the choice of research methods and tactics of interviewing the defendant depends on his/her psychological characteristics; increase the objectivity and reliability of expert opinions, i.e. the expert must take into account the possible influence of psychological characteristics on the defendant's behaviour and answers; avoid mistakes and bias in the examination (the expert must be objective and impartial). Psychological characteristics of a person are not static, they can change over time under the influence of various factors. Therefore, the expert must take into account not only the stable psychological characteristics of the defendant, but also his or her current emotional state. The study of psychological characteristics of a personality and their impact on the tactics of forensic psychiatric examination is important for improving the quality of examinations. Understanding these features allows the expert to assess the defendant’s mental state more objectively and reliably.

Проанализировано влияние психологических особенностей личности обвиняемого на тактику проведения судебно-психиатрической экспертизы. Исследованы конкретные аспекты личного состава личности, которые могут влиять на результаты экспертизы и как это учитывается при ее проведении. Сделан акцент на взаимодействии психологических факторов с правовыми процессами и возможности их учета для обеспечения объективности и точности судебных приговоров. Проанализированы практические аспекты работы экспертов в сфере судебной психиатрии и даны рекомендации по оптимизации процесса проведения экспертизы с учетом психологических особенностей личности обвиняемого.
The influence of psychological characteristics of a personality on the tactics of forensic psychiatric examination
Keywords: судово-психіатрична експертиза; психологічні особливості; особистість; тактика проведення експертизи; вплив психологічних чинників; forensic psychiatric examination; psychological features; personality; examination tactics; influence of psychological factors; судебно-психиатрическая экспертиза; психологические особенности; личность; тактика проведения экспертизы; влияние психологических факторов